A Case Study of Random Vibration Response Modeling of Two- Story-Building Due to Earthquake - Jweeg, Mohsin Juber; Ismail, Mahmud R.; R., Salah Aldein M. (Al-Nahrain Journal for Engineering Sciences, 2017)
In this work a general dynamic response of two-story building due to earthquake is investigated .A spatial case of two degree mass-spring–damper random vibration model is employed .The base excitation acceleration is represented according to the well- known_x000D_regression model  by Kanai –Tajimi in term of the power specturm density  (PSD). The transfer function between the ground an the roofs are evaluated assuming transverse modes of vibration._x000D_A case study of typical two symitrical story building manufactored from reinforced concret and steel is investigated.The vibration parameters such as effective mass and stiffiness and damping are calculated according  to the ACI 318-11 code.The natural frequncies , mode shape and transfer functions are calculated and plotted.The PSD acceleration at the roofs are evaluated from which the mean and standared diviation of the random accelration are found .The drift at the walls is calculated and compared with the allowable limits recommended by IBC 2015 .It is found that the probability of the bulding to be safe is  between (13.74 -7.35)% for the first story and (8.7 - 1.67) % for the second.